Flavonoid Myricetin Modulates GABAA Receptor Activity through Activation of Ca2+ Channels and CaMK-II Pathway. (11th November 2012) - Zhang, Xiao Hu; Ma, Ze Gang; Rowlands, Dewi Kenneth; Gou, Yu Lin; Fok, Kin Lam; Wong, Hau Yan; Yu, Mei Kuen; Tsang, Lai Ling; Mu, Li; Chen, Lei; Yung, Wing Ho; Chung, Yiu Wa; et al.
Abstract : The flavonoid myricetin is found in several sedative herbs, for example, the St. John's Wort, but its influence on sedation and its possible mechanism of action are unknown. Using patch-clamp technique on a brain slice preparation, the present study found that myricetin promoted GABAergic activity in the neurons of hypothalamic paraventricular nucleus (PVN) by increasing the decay time and frequency of the inhibitory currents mediated by GABA A receptor. This effect of myricetin was not blocked by the GABA A receptor benzodiazepine- (BZ-) binding site antagonist flumazenil, but by KN-62, a specific inhibitor of the Ca 2+ /calmodulin-stimulated protein kinase II (CaMK-II). Patch clamp and live Ca 2+ imaging studies found that myricetin could increase Ca 2+ current and intracellular Ca 2+ concentration, respectively, via T- and L-type Ca 2+ channels in rat PVN neurons and hypothalamic primary culture neurons. Immunofluorescence staining showed increased phosphorylation of CaMK-II after myricetin incubation in primary culture of rat hypothalamic neurons, and the myricetin-induced CaMK-II phosphorylation was further confirmed by Western blotting in PC-12 cells. The present results suggest that myricetin enhances GABA A receptor activity via calcium channel/CaMK-II dependent mechanism, which is distinctively different from that of most existing BZ-binding site agonists of GABA A receptor.